LINGO-CULTURAL CONSTRUCT IN DESCRIBING LINGO-CULTURAL STATE OF AFFAIRS - Karimova Dilorom Shavkat (Journal of new century innovations, 2022)
The matter of the link and interaction of language and culture has become central in science emerged within the middle of the last century at the confluence of sociolinguistics, ethno-linguistics, linguistic country studies, cultural studies – cultural linguistics. Main tasks of recent cultural linguistics are reflective national consciousness in the language, verbalizing cultural objects by means that of the language, sending valuable cultural classes in lexical meanings of words. to explain issues of language system functioning during a certain period and on a definite territory, one ought to refer to the ideas of a language scenario, a Lingo-Cultural situation that are perpetually developing, therefore, they will be characterized as stable or dynamic and represent a static fundamental measure of a definite linguistic culture that forms next similar periods.